Tontura em idosos da comunidade: estudo populacional exploratório - Moraes, Suzana Albuquerque de (2011)
INTRODUCTION: Dizziness is a common complaint amomg older population and its prevalence increases significantly with advancing age. There are several dizziness definitions and sensations in the literature, such as: general sensation of disorientation, ligth-headness sensation, floating, fuzzy, giddy, postural instability, or a sensation of motion when no motion is occurring. Dizziness is associated with a wide range of negative health outcomes , such as falls, disability, functional decline, depression, and poor quality of life. It has been considered a geriatric syndrome, with a multifactorial nature. OBJECTIVE: To explore dizziness complaint in the last year regarding the sociodemographic, physical and mental health and physical functioning variables in community-dwelling older adults. METHODS: Cross-sectional, population based study, with 391 men and women, 65 years and over living in an urban area in the municipality Cuiabá-MT. The outcome variable was the self report of dizziness in the last year. RESULTS: The prevalence of dizziness was 45%. Vertigo was reported by 70,4% of older adults and 43,8% reported any vertiginous crisis along life span. Dizziness was associated with female gender (p=0,004), memory problems complaint (p=0,015), poor subjective health perception (p=0,001), depression (p<0,0001), five or more comorbidities (p=0,021), fatigue (p<0,0001), recurrent falls (p=0,001), excessive daytime sleepiness (p=0,003), fear of falling (p<0,0001), left unipodal time stance (p=0,002) e Short Performance Physical Battery score (p=0,009). The multivariate regression analysis revealed that dizziness was associated with female gender (OR=1,72 95% IC 1,10-2,69), fatigue (OR= 1,90 95% IC 1,18-3,05), excessive daytime sleepiness (OR= 1,97 95% IC 1,16-3,37) and depression, (OR=2,18 95% IC 1,36-3,50). CONCLUSION: Almost half of the community-dwelling older adults reported dizziness. Dizziness related factors suggest its multifactorial nature and reassure the necessity of building trained human resources in primary health to reduce the negative impact of dizziness in the functionality and quality of life of older adults.